Astrocyte Stellation, a Process Dependent on Rac1 Is Sustained by the Regulated Exocytosis of Enlargeosomes - Racchetti, Gabriella (Wiley Subscription Services, Inc., A Wiley Company, 2012)
Cultured astrocytes exhibit a flat/epitelioid phenotype much different from the star-like phenotype of tissue astrocytes. Upon exposure to treatments that affect the small GTPase Rho and/or its effector ROCK, however, flat astrocytes undergo stellation, with restructuring of cytoskeleton and outgrowth of processes with lamellipodia, assuming a phenotype closer to that exhibited in situ. The mechanisms of this change are known only in part. Using the ROCK blocker drug Y27632, which induces rapid (tens of min), dose-dependent and reversible stellations, we focused on two specific aspects of the process: its dependence on small GTPases and the large surface expansion of the cells. Contrary to previous reports, we found stellation to be governed by the small G protein Rac1, up to disappearance of the process when Rac1 was downregulated or blocked by a specific drug. In contrast cdc42, the other G-protein often involved in phenotype changes, appeared not involved. The surface expansion concomitant to cytoskeleton restructuring, also dependent on Rac1, was found to be at least partially sustained by the exocytosis of enlargeosomes, small vesicles distinct from classical cell organelles, which are abundant in astrocytes. Exhaustion of stellation induced by repeated administrations of Y27632 correlated with the decrease of the enlargeosome pool. A whole-cell process like stellation of cultured astrocytes might be irrelevant in the brain tissue. However, local restructuring of the cytoskeleton coordinate with surface expansion, occurring at critical cell sites and sustained by mechanisms analogous to those of stellation, might be of importance in both astrocyte physiology and pathology. © 2011 Wiley Periodicals, Inc.